PTK2-mediated degradation of ATG3 impedes cancer cells susceptible to DNA damage treatment. Issue 3 (4th March 2017) - Ma, Ke; Fu, Wan; Tang, Ming; Zhang, Chaohua; Hou, Tianyun; Li, Ran; Lu, Xiaopeng; Wang, Yanan; Zhou, Jingyi; Li, Xue; Zhang, Luyao; Wang, Lina; et al.
ABSTRACT: ATG3 (autophagy-related 3) is an E2-like enzyme essential for autophagy; however, it is unknown whether it has an autophagy-independent function. Here, we report that ATG3 is a relatively stable protein in unstressed cells, but it is degraded in response to DNA-damaging agents such as etoposide or cisplatin. With mass spectrometry and a mutagenesis assay, phosphorylation of tyrosine 203 of ATG3 was identified to be a critical modification for its degradation, which was further confirmed by manipulating ATG3 Y203E (phosphorylation mimic) or ATG3 Y203F (phosphorylation-incompetent) in Atg3 knockout MEFs. In addition, by using a generated phospho-specific antibody we showed that phosphorylation of Y203 significantly increased upon etoposide treatment. With a specific inhibitor or siRNA, PTK2 (protein tyrosine kinase 2) was confirmed to catalyze the phosphorylation of ATG3 at Y203. Furthermore, a newly identified function of ATG3 was recognized to be associated with the promotion of DNA damage-induced mitotic catastrophe, in which ATG3 interferes with the function of BAG3, a crucial protein in the mitotic process, by binding. Finally, PTK2 inhibition-induced sustained levels of ATG3 were able to sensitize cancer cells to DNA-damaging agents. Our findings strengthen the notion that targeting PTK2 in combination with DNA-damaging agents is a novel strategy for cancer therapy.